Correlation between ESR and hs-CRP Levels with HbA1c in diabetes mellitus patients - Farah Adelia Qotrunnada; Anik Handayati; Museyaroh; Lully Hanni Endarini (JHeS (Journal of Health Studies), 2024)
Subclinical inflammation and almost every indication of systemic inflammation, which is defined by elevated levels of inflammatory markers in the blood, are seen in patients with diabetes mellitus (DM). Understanding the relationship between inflammatory markers and glycemic control is essential for creating comprehensive management strategies to avoid diabetes-related complications. The aims of this study were to determine the correlation between erythrocyte sedimentation rate (ESR) and high-sensitivity C-reactive protein (hs-CRP) and glycated hemoglobin (HbA1c) in DM patients. This was an analytical observational study with a cross-sectional design that was conducted on 35 DM patients from the DM prolanis group at the Bangkalan Regency First-Level Health Facility. HbA1c and hs-CRP levels were measured using the fluorescence immunoassay (FIA) method, while ESR was assessed using the Westergren method. Statistical analysis was performed using the Spearman correlation test. Regarding the biomarkers, all respondents (100%) had HbA1c levels >8.0%, 43% had elevated hs-CRP levels associated with cardiovascular risk, and 80% had abnormal ESR values. A significant relationship was found between ESR and HbA1c (p = 0.019; r = 0.394), but no significant relationship was observed between hs-CRP and HbA1c (p = 0.351; r = 0.163). The relationship between inflammation and glycemic control in DM can be understood through the correlation of ESR, hs-CRP, and HbA1c. These findings offer practical value, particularly in monitoring disease progression and managing diabetes-related complications. Future research should investigate the effects of interventions aimed at reducing inflammation, e.g lifestyle modifications or anti-inflammatory medications, on ESR, hs-CRP, and HbA1c levels.